(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
BRIC-African relation has been of interest to key stakeholders especially given the inclusion of South Africa. In the existing literature some researchers hypothesized inclusion of Nigeria will accelerate BRICS objective of enhancing market access to ensure rapid economic growth among other objectives. This study utilized daily exchange rates of Naira/Dollar together with BRICS Dollar exchange rate for a period of 18 years. The study aimed to determine the volatility spillover between Nigerian and BRICS nations via Multivariate GARCH family: VECH, DBEKK and CCC Models. The result of VECH and DBEKK Models showed that all parameters were significant at 5% level, indicating clearly that there is positive impact of Exchange Rate shocks of Nigeria on the Exchange Rate Volatility of the BRICS economies, while for the CCC model only one parameter was significant at 5% level. This clearly indicated the existence of positive impacts of Exchange rates shocks of Nigeria on the Exchange Rate Volatility of the BRICS economies. On the other hand, only VECH model was able to capture the volatility spillover (own and cross) both on negative direction, suggesting a causal relationship between past volatility shocks in Nigeria and current volatility in the BRICS economies. Conclusively based on the information above VECH model was found to be appropriate to capture the volatility spillover between Nigerian exchange rate and that of the BRICS nations.